Improving globally distributed software development and support processes – A workflow view. Issue 12 (19th June 2013) - Tunkelo, Teemu; Hameri, Ari‐Pekka; Pigneur, Yves
ABSTRACT We propose a new approach and related indicators for globally distributed software support and development based on a 3‐year process improvement project in a globally distributed engineering company. The company develops, delivers and supports a complex software system with tailored hardware components and unique end‐customer installations. By applying the domain knowledge from operations management on lead time reduction and its multiple benefits to process performance, the workflows of globally distributed software development and multitier support processes were measured and monitored throughout the company. The results show that the global end‐to‐end process visibility and centrally managed reporting at all levels of the organization catalyzed a change process toward significantly better performance. Due to the new performance indicators based on lead times and their variation with fixed control procedures, the case company was able to report faster bug‐fixing cycle times, improved response times and generally better customer satisfaction in its global operations. In all, lead times to implement new features and to respond to customer issues and requests were reduced by 50%. Copyright © 2013 John Wiley & Sons, Ltd.